INVOLVEMENT OF MINORS IN SUBVERTIVE ACTIVITIES AGAINST UKRAINE: CRIMINAL ANALYSIS OF WAR CRIMINAL PRACTICES IN CYBERSPACE (Bulletin of criminological association of Ukraine, 2025)
This article examines a pressing criminological issue: the involvement of Ukrainian minors in subversive activities against Ukraine orchestrated by Russian special services during the ongoing Russian-Ukrainian war. It highlights that, despite existing child protection systems, the war has exposed and intensified various profound problems across social, economic, informational, educational, familial, and law enforcement areas, which create conditions for the involvement of adolescents in criminal practices. The author analyzes official statistics and reports from law enforcement agencies in Ukraine, which indicate a concerning rise in subversive activities involving minors. Key indicators of this involvement include the use of digital platforms, selfish motivations, concealed intentions behind actions, and the employment of manipulative tactics. The article stresses the importance of implementing effective general and specialized criminological measures to combat these criminal activities. It emphasises the need for law enforcement initiatives, educational programs, public awareness campaigns, and protective measures to support vulnerable children. The author concludes by underscoring the critical role of the State in safeguarding children, viewing this commitment as vital for ensuring the future stability of the State and society during wartime.
Keywords: minors; war; involvement in illegal activities; subversion; recruitment; cyberspace; cybersecurity; crime; combating crime